Choosing railway Vehicles for carrying passengers - Dailydka, Stasys (Transport, 2010)
To carry passengers, diesel and electrical trains, railcars, passenger carriages and hauled locomotives are used in AB ‘Lietuvos geležinkeliai’ (Lithuanian Railways). In certain sections, the number of passengers is very low (e.g. several or up to twenty passengers per 24 hours), and therefore rolling stock is used inefficiently. For this reason, it is necessary to optimize the choice of vehicles on different routes taking into account the possibilities of their application and fluctuations in the number of passengers. To this end, a mathematical model has to be developed which would allow selecting an efficient means for carrying passengers in each case and, if required, to choose rational routes by applying the above introduced model.First published online: 27 Oct 2010